A response “Comment to Wetzeliella and its allies ― the ‘hole’ story: a taxonomic revision of the Paleogene dinoflagellate subfamily Wetzelielloideae by Williams et al. (2015).” - Williams, Graham L. (2017)
The paper by Williams et al. (2015) concerning a proposed taxonomic revision of the subfamily Wetzelielloideae has led to a Comment by Bijl et al. (2016) that questions the validity of our assumptions regarding recognition of the equiepeliform, latiepeliform, hyperepeliform and soleiform archaeopyle types nd their significance at the generic level. In this response we address the points that they raise, which are: the introduction of taxonomic criteria allegedly not followed in other fossil subfamilies; the erection of too many taxa; the unworkable nature of the proposed classification; and the reduction of stratigraphic applicability of many significant stratigraphic marker species. We have organized our response under the following topics: pragmatism versus theory; generic criteria: intergroup consistency; the genus Apectodinium and operculum attachment; stratigraphic utility; the number of taxa; and recognition problems. We also discuss specimens illustrated in the two plates included with the Comment. The variations in archaeopyle shapes and types of attachment of the operculum (the latter concept has been modified following more recent research) that we have used in part to separate the genera within the Wetzelielloideae have been previously applied to other peridiniaceans subfamilies, most notably the Deflandreoideae. As with that subfamily, we consider that our focus on archaeopyle shape and operculum attachment for differentiating wetzelielloidean genera introduces an approach that may help refine the stratigraphic ranges of individual species. While it is a fundamental truth that there are no ?correct? taxonomic ideas, we consider that new approaches should be tested with usage over time, not rejected out of hand prior to careful study.